Governors and local elites in Russia: patterns of interaction. Issue 3 (27th May 2019) - Ledyaev, Valeri; Chirikova, Alla
ABSTRACT: Empirical research conducted in 5 Russian local communities in 2011–2015 discovered asymmetric principal-agent relations between regional and municipal authorities in which regional authorities have all the necessary resources for effective control over the urban elites and interference in the local political process. However, despite the increasing centralization, the regional-local government relationships remain variable. The active presence or absence of the governor and his team in urban politics largely depends on personal relations between the heads of regional and municipal administrations, the resource base of the territory, the severity of conflicts and/or problems that threaten its stable development. Spectrum of relations between the regional and local elites varies from quite constructive and relatively conflict-free, to rather tense and open confrontation, while the interference of the regional authorities in the activities of the local government bodies differs from episodic to permanent.